Review Of Untoward Effects Of Impure And Malprocessed Bhasma And Their Management - Sharma, Rachana; Goyal, Manisha; Agarwal, Rajaram (International Research Journal of Ayurveda & Yoga, 2020)
Rasashastra plays an important role in Ayurveda. It’s a pharmaceutical branch of indian system of medicine. It deals mainly with various metals, minerals, mercury, animal products and other substances. In this text different types of shodhana and marana process are described for rasa, maharasa, uprasa, sadharana rasa, ratna, dhatu, upratnas etc. Bhasma is prepared by the marana process and it helps in easy absorption and assimilation due to micro fine element particles and does not produce any side effects in the human body, incinerated dravya will eradicate jara(old age), and diseases. Hence bhasma pareeksha like rekhapurana, apunarbhava, niruthaetc are also described in this text. Due to increase demand of rasaushadhis and commercialization, pharmaceutical companies are compromising with quality and standard of bhasma to prepare them in a short span of time, because processing of bhasma involves heavy labour and lot of tedious procedures like shodhana, mardana(bhawana), marana. If the shodhana process of metals and minerals is not done properly, then it acts as poison and reveals different types of complications in the human body like jwara, bhrama, vamana, kushtha, shool, mrityu etc. So in this article I described comparative analysis of heavy metal poisoning and its treatment. Comparative analysis of heavy metal poisoning and its treatment are mentioned in this article.